IMMEDIATE HEART RATE RESPONSE TO STANDING: A SIMPLE TEST FOR DIAGNOSIS OF AUTONOMIC NEUROPATHY IN DIABETES - Sandila, Muhammad Parwaiz; Chandio, Atta Muhammad; Ahmed, Syed Tousif; Rahu, Ali Akbar; Dahri, Amir Hamzo (Journal of Ayub Medical College Abbottabad, 2000)
Background: This work was done to study the usefulness of heart rate response to standing from a lying posture as a simple bedside/outpatient maneuver in patients with diabetic autonomic neuropathy. Methods: It was a prospective randomized study of 43 patients suffering from diabetes mellitus conducted at Diabetic outpatient clinic, Jinnah Postgraduate Medical Centre. Karachi. Results: The heart rate response, expressed as RR30/RR1 5 ratio in normal subjects was 1.20±0.01, in diabetics without autonomic neuropathy 1.18±0.01 and in diabetic with autonomic neuropathy 0.98±0.01. Resting heart rate per minute in normal subjects was 72.68±1.39, in diabetics without autonomic neuropathy 76.66±1.43 and in diabetics with neuropathy 87.54 ± 1.53. Both RR30/ RR15 ratio and resting heart rate in diabetic with autonomic neuropathy were highly significant (p<0.001) when compared with the corresponding values of normal subjects and diabetics without autonomic neuropathy. Conclusion: Heart rate response to change in posture is a useful and simple test that can be employed as a bedside or outpatient maneuver to diagnose autonomic neuropathy in diabetes by a conventional electrocardiogram